Ilmu Mukhtalif Al-?ad??: Pendekatan dan Metode Penyelesaian - Sheyla Nichlatus Sovia; Rendy Dwi Hermanto (Program Studi Ilmu Hadis STAIN Mandailing Natal, 2024)
The theoretical study of the contradictions that exist in the hadiths of the Prophet s.a.w. has begun since the 2nd century Hijri. The existence of mukhtalif (contradictory) hadiths regarding a particular problem, practically can cause confusion in taking certainty of the teachings (legal provisions) that regulate the problem, which of them must be followed and practiced. In order not to be trapped in understanding hadiths that appear to be contradictory, it is necessary to discuss a study of hadith, namely the Mukhtalif al-Had?th and its resolution. Mukhtalif al-Had?th is a science that seeks to bring together (talf?q al-had?th) several hadiths that contradict their meaning. Included in the definition of mukhtalif hadith are hadiths that are difficult to understand because of the existence of difficult-to-understand words. This article attempts to explore matters relating to the Mukhtalif al-Had?th as well as its approach and method of solution so that readers can draw conclusions not to rush to reject hadiths that are considered contradictory before actually conducting in-depth verification.